Exercícios teatrais inacianos: uma pesquisa por jogos teatrais transdisciplinares - Schaitel, Felipe Fernando (Universidade do Vale do Rio dos Sinos, 2021)
This article relates aspects of Ignatian Spirituality and Pedagogy with the language and teaching of Theater. It present 6 proposals and results of transdisciplinary games that exercise Ignatian values in pedagogical practice. The Ignatian principles worked on are: Action, Reflection, Contemplation, Magis, Self-knowledge, Sharing, the role of the student in his teaching-learning process, Experience, Integral Teaching, Cura personalis, Repetition, learning from others, transdisciplinarity, appreciation. These games are for teachers from all areas to appropriate and use in their classes. All exercises were tried out with the 6th grade classes of Colégio Catarinense in 2020 and 2021, from which I present photos of the research collection and students' reports with fictitious names. The methodology used for the exercise’s elaboration takes place through the dialogue between the way of Teaching Ignatian, based on the records of Father Klein and Teacher João Batista Storck, and references from the Theater field – such as the book Teatro do Oprimido, major legacy of Augusto Boal (1931 – 2009) and the result of his theater experiences in Brazil, Argentina and Peru. His practice is very rich and has great potential for transformation through experience, action and reflection. In the text, I go deeper into this activity and propose it as one of the Ignatian Theater Exercises. Furthermore, to support concepts of art education that elucidate the relationship between theatrical practice and sensitive learning, I associate this experience with the reports of the Art Educator Ana Mae Barbosa (1936 -), who suggests the Teaching of Arts as a learning tool for other disciplines, as I defend in this research.
Keywords: Exercícios espirituais; Pedagogia Inaciana; Arte-educação; Jogos teatrais; Transdisciplinaridade; Spiritual exercises; Ignatian pedagogy; Art education; Theatrical games; Transdisciplinarity